Use of cone beam computed tomography in the study of radicular morphology of maxillary premolars (Research, Society and Development, 2021)
The aim of this study is to investigate the morphology of maxillary premolar root canal systems using cone beam computed tomography. The literature review was carried out through a literature review of studies published in recent years in the databases of PubMed/Medline, Scopus, LILACS and SciELO. The results show that cone beam computed tomography allows the visualization of three-dimensional structures, reducing image overlapping and allowing a better identification of more complex and variable channel structures, such as premolars. The maxillary first premolars had one to two roots, with a prevalence of type IV and II root canal systems. The maxillary second premolars also varied in number of roots between single-rooted and double-rooted, and had a higher prevalence of type I, II and IV canals. It is possible to conclude that premolars are teeth with high root variability and cone beam computed tomography are a good instrument to help the study of these morphological variations, reducing the possibility of errors in endodontic treatments.